Jika \( f(x) = ax+3, \ a \neq 0 \) dan \( f^{-1}( f^{-1}(g) ) = 3 \), maka nilai \( a^2+a+1 \) adalah…
- 11
- 9
- 7
- 5
- 3
Pembahasan:
Berdasarkan informasi pada soal, kita peroleh berikut:
\begin{aligned} f(x) = ax+3 \Leftrightarrow y &= ax+3 \\[8pt] ax &= y-3 \\[8pt] x &= \frac{y-3}{a} \\[8pt] f^{-1}(x) &= \frac{x-3}{a} \\[8pt] f^{-1}(9) &= \frac{9-3}{a}=\frac{6}{a} \end{aligned}
Dari soal juga diketahui \(\) sehingga diperoleh:
\begin{aligned} f^{-1} \left( f^{-1}(9) \right) &= 3 \\[8pt] f^{-1} \left( \frac{6}{a} \right) = 3 \Leftrightarrow \frac{ \frac{6}{a}-3}{a} &= 3 \\[8pt] \frac{6}{a}-3 &= 3a \\[8pt] 6-3a &= 3a^2 \\[8pt] 3a^2+3a-6 &= 0 \\[8pt] a^2+a-2 &= 0 \\[8pt] a^2+a+1 &= 3 \end{aligned}
Jawaban E.